التعلم القائم على القراءة والكتابة في تحسين مهارات القراءة والكتابة باللغة العربية في المدرسة الثانوية بني رانجانغ سومبرآسيه بربالينجا - Ilmiyantita, Annisa’ Mazroatul; Yunus, Moch; Shobirin, Shobirin (ISLAMIKA, 2024)
This research aims to investigate the success of learning that focuses on literacy in improving Arabic reading and writing skills at SMA Bani Rancang Sumberasih Probolinggo. This research will apply literacy learning strategies effectively in the context of Arabic language learning. This method uses a descriptive qualitative approach. Data collection techniques include interviews, assignments and the results of researcher observations. The results of this literacy-based learning show the enthusiasm of the students and obtain two answers, namely: 1. Effective, they listen and pay attention from the beginning to the end of the lesson. 2. Attractive, they are enthusiastic and even able to think creatively in carrying out the tasks given.